Single-switch single-phase boost power factor correction circuit with harmonic current reduction - Khan, , P. K. Shadhu; Athab, , Hussain S. (2006)
In this paper a duty cycle modulation using second-harmonic injection method for single phase boost converter has been described. In this method, a second harmonic signal is injected to reference saw-tooth wave carrier instead of the output voltage control signal. As a result, an amplitude modulation of the reference signal is obtained which eventually modulates the duty cycle of the power switch. The injected signal is synchronized with input ac voltage and the dosed loop feedback control of the boost converter is not affected by the proposed open loop harmonic injection method. Simulation and experimental results are presented to confirm the validity of the method.